The Revitalization of Batu Parsidangan Batak Toba Folklore Into Teaching Materials in English Subject for Junior High School - Fungky Lusiana Sinamo; Bambang Nur Alamsyah Lubis; Thesa Ayu Emalinta Barus; Syeba Jenita Sembiring (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research aims to find out the original story of Batak Toba folklore “Batu Parsidangan” and transformed it into a script as teaching material in junior high school. This research was conducted at Batu Parsidangan, Desa Siallagan Pindaraya, Kabupaten Samosir, North Sumatera. This research used descriptive qualitative method to describe words and clauses systematically, accurately, and factually. The instrument of data collection was observation, interview and documentation. The source of data were Bataknese informant. The result of this research is Batu Parsidangan was used by the Batak King to punish and execute the defendant who does the criminals in his village. Keywords : Folklore, Batu Parsidangan, Revitalization, Teaching Materials